# Problem 1.

2: Give an  − δ proof that

X 1
xn =
1−x
n=0

when |x| < 1.

Proof. The sequence of partial sums of the series is given as follows:

(1, 1 + x, 1 + x + x2 , . . . , 1 + x + x2 + · · · + xk−1 , . . .).
1
We proceed by showing that the sequence of partial sums converges to 1−x when |x| < 1. Let  > 0 be
l m
log[(1−x)]
given and choose δ = log x . Letting k > δ implies that k log x > log[(1 − x)]. When |x| < 1,

xk
< .
1−x

2 k−1

.

.

.

.

1 + x + x2 + · · · + xk−1 − 1 .

= .

(1 − x)(1 + x + x + · · · + x ) − 1 .

.

.

.

.

.

1 − x.

.

1−x .

x2 ) + dY (y1 . y1 ) which implies d(z1 . z2 ) = dX (x1 . x2 ) + dY (y1 . . y2 ).4: Suppose that (X. y2 ) ≥ 0 which implies d(z1 . y3 ) + dY (y3 . x3 ) + dX (x3 . y2 ). Proof. z2 ) = 0 if z1 = z2 . x2 ) = d(y1 . y2 ) = 0. 1−x Problem 1. y2 ) = dX (x2 . z2 ) which shows the triangle inequality for d. Prove that the Cartesian product Z = X × Y is a metric space with metric d defined by d(z1 . z2 ) = d(z2 . x2 ) + dY (y1 . z1 ). z1 ) = 0 implies that d(z1 . x2 ) + dY (y1 . y2 ) ≥ 0. xk = . By the symmetry of dX and dY . x2 ) + dY (y3 . x3 ) + dY (y1 . x2 ) + dY (y1 . the triangle inequality for dX and dY implies dX (x1 . dX (x1 . d(z1 then z2 ) = 0 which is obtained from the fact that x1 = x2 and y1 = y2 imply that d(x1 . where z1 = (x1 . y1 ) and z2 = (x2 . Finally. 1−x So we conclude that xk < . y1 ) = 0 therefore d(z1 . Since dX (x1 . x1 ) + dY (y2 . dY ) are metric spaces. y2 ) ≤ dX (x1 . y2 ) ≤ d(z1 . x1 ) + dY (y1 . z3 ) + d(z3 . dX ) and (Y. y3 ) + dX (x3 . We also obtain that dX (x1 . y2 ) ≤ dX (x1 . z2 ) ≥ 0. dX (x1 . x2 ) ≥ 0 and dY (y1 . Backward implication shows that if z1 = z2 .

Since kx − yk ≥ 0 and kx − yk = 0 if and only if x = y. y) is symmetric. . Prove that (1. s ≥ N ⇒ |vjr − vjs | < n . y) = kx − yk is a metric on X. Each component (vik ) is a sequence in R. . kx − yk 1 ≤1− 1 + kx − yk kx − zk + kz − yk + 1 kx − zk + kz − yk ≤ 1 + kx − zk + kz − yk kx − zk kz − yk kx − zk kz − yk ≤ + ≤ + 1 + kx − zk + kz − yk 1 + kx − zk + kz − yk 1 + kx − zk 1 + kz − yk which shows the triangle inequality of a metric. + |vnk − vnl + vnl | ≤ |v1k − v1l | + |v2k − v2l | + |v3k − v3l | + . kx − yk ≥ 0.4) define metrics on X. prove that Rn equipped with the sum. 1 + kx − yk kx − yk | − 1|k − x + yk ky − xk = = 1 + kx − yk 1 + | − 1|k − x + yk 1 + ky − xk so we conclude that d(x. Proof. v3k . y) = =0 1+0 if and only if x = y.Problem 1. . . kx − yk = kx − z + z − yk ≤ kx − zk + kz − yk kx−yk which satisfies the triangle inequality of a metric. . Proof. vnk ). we can naturally define a sum norm on Rn as kvk = |v1k | + |v2k | + |v3k | + . v2k . Since kx − yk ≥ 0 and 1 + kx − yk > 0. ∀ > 0 ∃N ∈ N such that r. . In components vk = (v1k . k · k) is a normed linear space. . . the non-negativity condition of a metric is satisfied. kx − yk = | − 1|k − x + yk = ky − xk which shows that the norm is symmetric thus satisfying the symmetry condition of a metric. y) = 1+kx−yk is a metric on X.2) and (1. maximum. |v1k − v1l + v1l | + |v2k − v2l + v2l | + |v3k − v3l + v3l | + . . + |vnk − vnl | + kwk . Suppose (vk ) is a Cauchy sequence of vectors in Rn . + |vnk |. Finally. We first show that d(x. Since R is complete.6: Starting from the fact that R equipped with its usual distance function is complete. or Euclidean norm is complete. we show that d(x. Furthermore. Problem 1. kx − yk = 0 if and only if x = y therefore 0 d(x. .5: Suppose that (X.

Problem 1. Comparing the Euclidean to the sum norm we get that kxkE ≤ kxks . Comparing the Euclidean and the maximum norms we get that kxkm ≤ kxkE . x3 . maximum and Euclidean norms is equivalent. we conclude Rn is complete with respect to the sum norm. By lemma 1. Hence. we have shown the convergence of any sequence in Rn is equivalent. n→∞ n→∞ Proof. xn ≤ bn implies n→∞ inf bn ≥ inf xn thus lim inf bn ≥ x. To see this. kvk − kwk ≤ /n + /n + /n + . Proof. n→∞ .Therefore. The maximum norm will pick out x1 while the Euclidean computes the square root of the sums of squares of all other xi ’s. . square the sum norm and the take the square root. To see this.11: If (xn ) is a sequence of real numbers such that lim xn = x. Convergence of any sequence in Rn with respect to the sum. x2 . . By bounding the norms through the inequalities above. prove that lim sup an ≤ x ≤ lim inf bn . Lemma 1. .6 we also conclude that Rn is also complete with respect to the maximum and Euclidean norms. xn } q kxkE = x21 + x22 + x23 + · · · + x2n . + /n = . sup an ≤ sup xn which implies lim sup an ≤ x. Likewise. | {z } n times From the reverse triangle inequality |kvk − kwk| ≤ kv − wk which implies that |kvk − kwk| ≤ kv − wk ≤ kvk − kwk ≤ . . n→∞ and an ≤ xn ≤ bn .6. We therefore conclude that kxkm ≤ kxkE ≤ kxks ≤ nkxkm . Since xn ≥ an . maximum (k·km ) and Euclidean (k·kE ) norms of a vector x are defined respectively as kxks = |x1 | + |x2 | + |x3 | + · · · + |xn | kxkm = max{x1 . . The sum (k·ks ). . The maximum norm is equal to the sum norm if and only if the all other xi ’s are zero. Squaring the sum norm results in cross terms which increases its size compared to the Euclidean norm. assume that x1 is greater than all other xi ’s. This shows the convergence of the Cauchy sequence.